Volatility Analysis of International Tourist Arrival Growth Rates to Thailand using Garch and GJR Model - BUNNAG, Tanattrin (Journal of Environmental Management and Tourism, 2016)
This paper examined volatility of international tourist arrival growth rates to Thailand using monthly time series data for the period 1979-2010. The variable of interest for policy maker was the tourist arrival growth rates at any given month as this figure was directly related to tourism revenue growth rates. In this study we considered the volatility of international tourist arrival growth rates to Thailand by employing GARCH and GJR model. GARCH and GJR model were widely used to manage the risk exposure of financial and tourism risk. Considering the number of tourist arrivals and growth rate of tourist arrivals, it was found that the majority of tourists were from Malaysia and Japan. This study could be used to compare with the USA and the UK for making policy because of the difference in tourism volatility. From this study the GARCH model generated relatively accurate tourism volatility forecasts except for the Japan and the USA volatility, and the GJR model generated relatively accurate tourism volatility forecasts except for the Malaysia and the UK volatility.
Keywords: volatility; GARCH model; GJR model; tourism risk; growth rate of tourist arrivals